Variation in Species Richness and other Vegetational Parameters in Pine and Mixed Broadleaf Forest of Central Himalaya - Arya, Neeta (International Journal of Environment, Agriculture and Biotechnology, 2019)
In the present study total two forest stand on different canopy cover (open canopy, moderate canopy and close canopy) were studied to assess the importance of these two parameters in supporting species regeneration and biodiversity in a P. roxburghii forest and mixed broadleaf forest between 1300 and 2000 m elevation in the Utrarakhand Himalaya. Tree species richness was high in mixed broadleaf forest compared to P. roxburghii forest. While, shrub and herb species richness was high in P. roxburghii forest. The tree and herb density was significantly high in mixed broadleaf forest. Tree shrub and herb diversity was high in mixed broadleaf forest. These forests are exploited variously for different resources and consequently the vegetation cover is decreasing. The disturbances are changing the species richness and diversity, which influences the soil and environmental conditions. Thus, the conservation and management of these forests will be important for the sustainability of human and land. Disturbances and climate change will alter the species composition of these forests, which may shift socio-economic and ecological condition of the region.